2011
DOI: 10.1177/1049732311405066
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Living With Diabetes Following a Self-Management Program Based on Motivational Interviewing

Abstract: Self-management is an important part of diabetes treatment, but the promotion of self-care activities is still a challenge. In this study, we explored how living with diabetes in everyday life was experienced following a self-management intervention program based on motivational interviewing. We conducted seven focus group interviews, each comprising 3 to 5 participants diagnosed with type 1 or type 2 diabetes. Data analysis based on a phenomenological method revealed three main themes concerning diabetes self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…This dilemma between taking part in a normal life and managing the consequences of diabetes has been discussed in terms of other aspects of diabetic management [16,18]. Described in the current study as the self-perception dilemma, Beattie and colleagues [21] observed similar behaviour (termed ‘strategic adherence’), in a comparable patient group.…”
Section: Discussionsupporting
confidence: 54%
“…This dilemma between taking part in a normal life and managing the consequences of diabetes has been discussed in terms of other aspects of diabetic management [16,18]. Described in the current study as the self-perception dilemma, Beattie and colleagues [21] observed similar behaviour (termed ‘strategic adherence’), in a comparable patient group.…”
Section: Discussionsupporting
confidence: 54%
“…Supporting the notion of data sharing through the use of mobile applications are studies by Rossi et al () and Waite et al () who reported this feature as being a motivator to use mobile applications. Individuals with T1DM require support from their HCP in maintaining independent control of their condition which may be facilitated by incorporating this type of feature in any new technology design (Minet, Lonvig, Henrikson, & Wagner, ; Rankin et al, ; Ridge, Treasure, Forbes, Thomas, & Ismail, ).…”
Section: Discussionmentioning
confidence: 99%
“…; Minet et al . ) consider paternalistic relationships between clinicians and patients. All of this can serve to internalise notions of ‘good’ and ‘bad’ ways of living with diabetes.…”
Section: Attempting To Manage Diabetic Encountersmentioning
confidence: 99%